International Journal of Impotence Research Your Sexual Medicine Journal - can Serefoglu, Ege.; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Springer Nature.)
IJIR: Your Sexual Medicine Journal addresses sexual medicine for both genders as an interdisciplinary field. This includes basic science researchers, urologists, endocrinologists, cardiologists, family practitioners, gynecologists, internists, neurologists, psychiatrists, psychologists, radiologists and other health care clinicians. Areas of interest include clinical, treatment, basic science and special problems.
Keywords: Medicine; Reproductive medicine; Urology; Andrology; Medicine/Public Health, general; Urology; Reproductive Medicine; Andrology